Green space and cardiovascular health in people with type 2 diabetes. (May 2021) - Astell-Burt, Thomas; Navakatikyan, Michael A.; Walsan, Ramya; Davis, Walt; Figtree, Gemma; Arnolda, Leonard; Feng, Xiaoqi
Abstract: Associations between green space type and 9-year risk of incident cardiovascular disease (CVD) hospitalisations and deaths were analysed in 4166 people with type 2 diabetes in the Sax Institute's 45 and Up Study. Incidence of all-cause mortality, cardiovascular mortality, fatal or non-fatal CVD events and acute myocardial infarctions (AMI) were 14.67%, 7.23%, 47.36%, and 4.51%, respectively. After full adjustment, more tree canopy was associated with lower CVD mortality, lower fatal or non-fatal CVD events, and lower AMI risk. More open grass was associated with lower all-cause mortality, lower CVD mortality and lower fatal or non-fatal CVD events, but higher AMI risk. Highlights: Environmental risks for prevention of CVD in 'high risk' groups are under-studied. Hospital and death data were linked to a cohort and measures of green space type. Tree canopy and open grass were associated with lower CVD event and mortality risk.